2019
DOI: 10.1038/s41416-019-0548-9
|View full text |Cite
|
Sign up to set email alerts
|

Signet ring cell colorectal cancer: genomic insights into a rare subpopulation of colorectal adenocarcinoma

Abstract: Background Signet ring cell carcinoma (SRCC) is a rare subtype of colorectal cancer (CRC). The aim of this study was to characterise the genomic alterations and outcomes of SRCC. Methods Medical records of metastatic CRC (mCRC) patients whose tumours were evaluated by NGS analysis were reviewed. SC-mCRC were classified into two groups: SRCC (>50% signet ring cells) and adenocarcinoma (AC) with SC component (≤50% signet ring cells). Results Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
67
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 33 publications
6
67
2
1
Order By: Relevance
“…1D). Lower mutation rates of PIK3CA and KRAS in SRCC have also been reported recently (Korphaisarn et al, 2019). The phospho-ERK and phospho-S6 signals, indicators of MAPK and PI3K activities respectively, were much lower in SRCC, which was consistent with mutation data (Fig.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…1D). Lower mutation rates of PIK3CA and KRAS in SRCC have also been reported recently (Korphaisarn et al, 2019). The phospho-ERK and phospho-S6 signals, indicators of MAPK and PI3K activities respectively, were much lower in SRCC, which was consistent with mutation data (Fig.…”
supporting
confidence: 90%
“…1C,1D, S4 and S5). APC mutation was most prevalent in AC (∼80%) and MAC (∼70%) (TCGA, 2012), whereas it only occurred in one (3.4%) hypermutated SRCC, this is consistent with recent reports (Nam et al, 2018;Korphaisarn et al, 2019). Interestingly, SRCC was associated with frequent mutations in RNF43, with nonsense mutations (p.Glu43* and p.Arg132*) enriched at the N-terminus, regardless of mutation burden ( Fig.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Primary colorectal signet-ring cell carcinoma has distinct molecular features [17], aggressive behavior and worse prognosis[18] as compared to other histological subtypes. Our study found that primary tumor resection only decreased 37.7% mortality risk for patients with signet ring cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Primary colorectal signet-ring cell carcinoma has distinct molecular features [17], aggressive behavior and worse prognosis [18] as compared to other histological subtypes. Our study found that primary tumor resection only decreased 37.7% mortality risk for patients with signet ring cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%